INTERPRETASI VARIASI LEKSIKON UPACARA ADAT DALAM TRADISI MASYARAKAT KAMPUNG NAGA: KAJIAN ETNOLINGUISTIK - Ayda Nur Haliqa Nasution; Putri Sabrina; Faras Nabila; Marsela; Nabilah Maulana (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
Kampung Naga in Tasikmalaya, West Java, is a traditional community known for its commitment to preserving classical values and local wisdom. This tradition is reflected in various traditional ceremonies such as Hajat Sasih, but the linguistic elements or lexicon used are often overlooked and have not been documented. This study aims to identify and describe the lexicons used in Kampung Naga traditional ceremonies. Additionally, it seeks to enrich the study of ethnolinguistics and cultural anthropology with empirical data on the lexicon of traditional ceremonies of the Kampung Naga community. This study uses a descriptive qualitative approach with the main source of data coming from in-depth interviews with guides and traditional leaders in Kampung Naga, who provided information about the types, functions, and cultural values of the lexicon. The results of the study show that there are 16 traditional ceremony lexicons. These lexicons are divided into four types of linguistic units: monomorphemic words (such as lebe and nadran), polymorphic words (such as beberesih and unjuk-unjuk), noun phrases (such as bumi ageung and ijab kabul), and verb phrases (such as membersihkan makam). These lexicon not only function as a means of communication, but also reflect the cultural, spiritual, and environmental values of the local community. This research provides a new perspective with its in-depth focus on the linguistic aspects of traditional ceremonies, which is a significant contribution to the preservation of regional languages and cultures amid the threat of modernization.